An Uncommon Cause of Leg Swelling After Exercise: A Case Report on An Unprovoked Deep Vein Thrombosis in Young Healthy Man - Rathika Rajah; Alvin Oliver Payus; Norlaila Mustafa (2020)
Antiphospholipid syndrome is a hypercoagulable autoimmune condition that predominantly affect the female and commonly manifest as arterio-venous thrombosis and recurrent miscarriage. Here, we present a unique case of a healthy young man who developed sudden onset of right leg swelling after exercise which was then found to be due to deep vein thrombosis via Doppler ultrasound. His blood investigations showed thrombocytopenia and prolonged coagulation profile. Therefore, antiphospholipid syndrome was suspected and later confirmed by positive autoimmune antibodies. He was treated with long term moderate intensity oral warfarin. The objective of this case report is to share the uncommon occurrence of an unprovoked deep vein thrombosis secondary to antiphospholipid syndrome in a healthy young man so that the possibility of deep vein thrombosis should be suspected in selected cases of non-resolving leg swelling after exercise as it can lead to fatal pulmonary embolism.